A new Middle Pleistocene cranium in an Acheulian context at Gruta da Aroeira (Almonda karst system, Torres Novas, Portugal) - Daura, Joan (2018)
Despite the abundant remains from Sima de los Huesos and Arago, human cranial variability in the earlier Middle Pleistocene of Europe is poorly known, which makes it difficult to assess patterns of human diversity and possible regions for ancestral populations associated with the western Eurasian spread of the Acheulian technocomplex. A recently discovered partial cranium from the Gruta da Aroeira may shed some light on this period. U-series dating of stratigraphically overlying flowstone provides a minimum age of 390 ka, placing the fossil in the relevant time period . This cave site was first excavated between 1998 and 2002, revealing a rich collection of Acheulian bifaces in association with large mammals and two human teeth [1-2]. Work resumed in 2013, intent on reaching bedrock and establishing the chronology of the stratigraphic sequence, which, at the back of the cave, spans 4 m and comprises three major stratigraphic units. Unit 1 is a colmatation breccia. Unit 2 is a 2.2 m-thick mud-supported breccia rich in angular and sub-rounded clasts comprising Acheulean layer X. Basal unit 3 is a fluvial cave deposit comprising two layers: XI, with faunal remains but no artefacts; XII, sterile. The layer X lithics include handaxes and other bifacial tools; the Levallois method was not used. The highly fragmented faunal remains are dominated by cervids and equids and include Rhinocerotidae, bear, a large bovid, a caprid, and tortoise. Burnt bone fragments were recovered at the base of layer X. A partial human cranium encased in rockgrade breccia was discovered at the base of layer X. It consists of a large part of the right side of a braincase, lacking the occipital bone, but also preserving a portion of the left side of the frontal squama and supraorbital torus, as well as the interorbital region, including the vertical part of the nasal bones. A fragment of the right maxilla, with two molars partially preserved, was also found attached to the calvarium but not in anatomical position. Based on the degree of synostosis of the right coronal suture, the individual was a mature adult. There is no plastic deformation of the preserved regions although an extensive area of the outer surface of the frontal squama and the supraorbital torus was mechanically eroded (abraded) before final deposition, indicating a certain amount of transportation. As a consequence of the abrasion, the frontal squama was considerably thinned and the midorbital and lateral (trigone) parts of the supraorbital arches are lost. The fossil was mechanically removed from the breccia with great care and accuracy, and then CT-scanned and virtually reconstructed, using the Mimics v.18 software program. Although neither the sagittal suture nor bregma are preserved, there remains enough of the right portion of the frontal bone (including the interior frontal crest) to identify the midline. The preserved portions were mirror-imaged and the main transverse neurocranial diameters were measured. The Aroeira skull shows relatively thick bones, and an angular torus is present on the right parietal bone. This latter feature is a primitive trait found on some Middle Pleistocene fossils from the Sima de los Huesos , Caune de l’Arago and Ceprano, but not found in Neandertals and is consistent with a geological age between 400 ka and 500 ka. When the reconstructed braincase is viewed posteriorly, the parietal walls are fairly vertical but converge slightly towards the top. The general measurements of the Aroeira neurocranium are well within the ranges of the Sima de los Huesos (Atapuerca) collection and other European fossils attributed to the mid Middle Pleistocene, although the thickness of the supraorbital torus and the interorbital breadth are outstanding.